Implementation Of The Andragogy Approach To Improve Students' Arabic Understanding - Muhammad Muhlis; Umi Sumbulah; Agus Maimun; Ahmad Barizi (Ijaz Arabi Journal of Arabic Learning, 2023)
Andragogy learning is an art of learning approach with an adult-style practice. This approach is for students lacking attention to materials, learning orientation, self-concept, and learning motivation, especially in learning in Islamic boarding schools. This study aims to find the concept of andragogy learning in improving Arabic understanding. The subject is Ngalah Islamic boarding school Pasuruan School, Indonesia by using a qualitative approach with natural methods. The role of the researcher is to plan, collect, analyze and report research results. The data sources of this research were taken from interviews, observations, and documentation with orientation, exploration, and focused study with data analysis techniques: condensation, display, conclusion drawing, and data verification. The validity checking of the data is done with credibility, dependability, and confirmability. Research findings at Ngalah Islamic boarding school pasuruan include: a) orientation to the cultivation of tasawuf values (tariqat) with empirical, intuitive and tazkiyyah methods; b) respect is given in the form of muroqabah, riyadhoh, mujahadah and contemplation; c) learning motivation appears in the form of innovation and seeking wisdom. The learning orientation is relevant to the problem centered and contextual; learning readiness is relevant to autonomous, self-directing, resource, and mental models; and learning motivation is relevant to the value and personal payoff. The implications of andragogy learning at the Ngalah Islamic boarding school are increasing students' understanding of Arabic with an andragogy approach.